MERINTANGI PENGUBURAN JENAZAH COVID-19 DITINJAU BERDASARKAN PASAL 178 KITAB UNDANG-UNDANG HUKUM PIDANA - Muhammad Rezky Rinaldy dan Syamsudin (Universitas 17 Agustus 1945 Samarinda, 2020)
Indonesia and even the world now feel the impact of the Corona virus outbreak (covid-19), in connection with it hindering the burial of the bodies of victims who died. The phenomenon of corpse rejection of corona virus patients (covid-19) continues to occur in various regions. In fact, the body must be buried immediately no later than 4 hours after being declared dead. The main reason people are reluctant to accept the bodies of patients co-19 because of fear of contracting. While the medical ensure that the body will not transmit the virus. The body in the coffin has been wrapped and declared sterile. The type of research used in this study is the type of normative legal research, which is a legal research method that uses a statutory approachThe results of the study showed that obstructing officers who will carry out official burials could indeed be convicted. Law enforcement officials can use Article 178 of the Criminal Code. not a complaint offense. Law enforcement officials can immediately take action without anyone complaining.